Later Sunset, Better Health? - Shobhit Kulshreshtha; Leena Bhattacharya; Padmaja Ayyagari (Global Labor Organization (GLO), 2025)
Previous research, focusing primarily on high income countries, has linked later sunsets to sleep deficits and worse health outcomes. These results might not generalize to low- and middle- income countries, which have different socioeconomic, cultural, and environmental conditions. Using data from the 2015-16 and 2019-21 waves of India's Demographic and Health Surveys (DHS) and exploiting within-district variation in annual average sunset times, we estimate the causal impact of later sunsets on the long-term health outcomes of individuals. We find that later sunsets leads to a lower prevalence of anemia, diabetes, and thyroid disorders and an improvement in the overall health index. To explore mechanisms, we analyze variation in time allocation due to a later sunset time using the 2019 Time Use Survey. We find that individuals experiencing later sunsets sleep better and exercise more, but do not change their sedentary leisure activities. Additionally, they consume healthier food and increase labor supply. These lifestyle changes may explain the health improvements associated with delayed sunsets in India.
Keywords: J22; I12; I14; 330; health; sunset time; time use; lifestyle; fixed effects